Control of arm movement after bilateral lesions of area 5 in the monkey (Macaca mulatta). - Nixon, P; Burbaud, P; Passingham, R (1992)
The effect of bilateral area 5 lesions on the analysis of proprioceptive information and the guidance of reaching movements was studied in three rhesus monkeys. In the first paradigm (Proprioceptive discrimination test) the monkeys were trained to discriminate between movements of a joystick to the right or left without visual control; they reported the direction of movement by touching or not touching a screen (go/no-go task). After area 5 had been removed, the monkeys were only mildly impaired on this test. It is concluded that such simple joint movement could be analysed in area 2, area 5 being concerned with more complex arm movements. In the second paradigm (Searching test) the monkey had to find a peanut on a board in the dark using proprioceptive information stored in memory during previous trials. After area 5 lesions, the number of correct reaches was not modified but the number of errors after an incorrect trial (correcting movement) was significantly increased. The data suggests that when visual input is not available, area 5 is involved in the guidance of arm movements on the basis of proprioceptive inputs.